Bipolar net charge type composite polymer film with huge equivalent piezoelectric effect formed by utilizing micro-wrinkle design and preparation method of bipolar net charge type composite polymer film
By forming a micro-pleated array and pore cavity between the charge storage layer and the charge encapsulation layer, and forming a bipolar net charge by using Pashen polarization, the problem of small equivalent piezoelectric coefficient of the existing piezoelectric polymer is solved, and flexible and efficient charge output is achieved.
Patent Information
- Application Number
- CN202510590226.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-08-08
AI Technical Summary
The equivalent piezoelectric coefficient of existing piezoelectric polymer materials is small, complex in preparation and large in structure, making it difficult to meet the needs of flexible applications.
Using micro-pleat design and corona polarization treatment, a micro-pleat array and pore cavity are formed between the charge storage layer and the charge encapsulation layer, and a bipolar net charge is formed using Pashen polarization to form a macroscopic dipole to produce a huge equivalent piezoelectric effect.
It realizes a polymer film with a huge equivalent piezoelectric effect, with good structural flexibility and can output a large amount of charge under small external forces, which is suitable for a variety of application scenarios.
Smart Images

Figure CN120456805A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of piezoelectric polymers, and in particular relates to a bipolar net-charge composite polymer film having a huge equivalent piezoelectric effect formed by utilizing a micro-fold design, and a preparation method thereof. Background Art
[0002] With the rapid development of piezoelectric materials and other disciplines, piezoelectric polymers are finding widespread application in signal sensing, energy harvesting, and micro-displacement actuation. Researchers are dedicated to developing piezoelectric polymers with large equivalent piezoelectric coefficients. Piezoelectric electrets, as flexible functional materials with large equivalent piezoelectric coefficients, have important applications in the preparation of piezoelectric polymers. However, currently used piezoelectric polymer materials have relatively small equivalent piezoelectric coefficients, are complex to prepare, and have relatively large structural dimensions. Summary of the Invention
[0003] In order to overcome the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a polymer film with a huge equivalent piezoelectric coefficient and a preparation method, which utilizes the interlayer micro-wrinkle design and corona poling treatment of the pore cavity to generate a large number of directionally arranged macroscopic dipoles, thereby generating a huge equivalent piezoelectric effect. At the same time, the polymer film also has the characteristics of structural flexibility and lightness.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A bipolar net charge composite polymer film with a large equivalent piezoelectric effect is formed using a micro-corrugation design. The film comprises a charge storage layer 1, a first charge encapsulation layer 2-1 and a second charge encapsulation layer 2-2 attached to the upper and lower surfaces of the charge storage layer 1, respectively; a first electrode 3-1 attached to the upper surface of the first charge encapsulation layer 2-1; and a second electrode 3-2 attached to the lower surface of the second charge encapsulation layer 2-2. The surface of the charge storage layer 1 forms a surface micro-corrugation array through thermal stress release during template hot pressing, thereby improving the net charge storage capacity and the stability of large amounts of charge stored for a long time. Charges are converted into bipolar net charges through Paschen polarization and stored in the cavity between the first charge encapsulation layer 2-1, the second charge encapsulation layer 2-2, and the charge storage layer 1. The opposite-sign charges on the upper and lower surfaces of the cavity form a macroscopic dipole, which in turn produces a piezoelectric-like effect externally. By connecting the first electrode 3-1 and the second electrode 3-2 to an external circuit loop, the charge output under different stress conditions can be measured.
[0006] Micro-wrinkles are formed on the upper and lower surfaces of the charge storage layer 1 after hot pressing. There are two ways in which the micro-wrinkles are formed: one is the array concave-convex structure caused by the distributed pressure formed by the wire mesh on the charge storage layer 1, and the other is the thermal stress caused by rapid heating and pressurization during hot pressing. The thermal stress in the film is released after the hot pressing is completed, resulting in the formation of tiny wavy wrinkles on the surface; the two wrinkles have different scales and together constitute micro-wrinkles with a large equivalent surface area; the first charge encapsulation layer 2-1 and the second charge encapsulation layer 2-2 are bonded to the charge storage layer 1 to form a large number of pore cavities, and provide a huge equivalent piezoelectric coefficient after corona poling.
[0007] The method for preparing a bipolar net-charge composite polymer film having a huge equivalent piezoelectric effect by utilizing a micro-fold design comprises the following steps:
[0008] Step 1: Preparing a charge storage layer 1 and a first charge encapsulation layer 2-1 and a second charge encapsulation layer 2-2: The charge storage layer 1 uses a polymer material, polyvinylidene fluoride-co-trifluoroethylene powder, as a raw material. The powder is dissolved in an organic solvent, N,N-dimethylformamide, and spin-coated on a flat substrate. The powder is then thermally deposited at an ambient temperature of 70°C or above to form a polymer film with a thickness of 30-120 microns, serving as the charge storage layer 1. The first charge encapsulation layer 2-1 and the second charge encapsulation layer 2-2 use an electret material as a raw material and are formed by chemical deposition and solution precipitation methods to form polymer films with a thickness of 10-30 microns.
[0009] Step 2: After the charge storage layer 1 is prepared, it is hot-pressed using a wire mesh with different pore densities to form a surface micro-wrinkle array. Polydimethylsiloxane is used as a flexible hot-pressing substrate, and the charge storage layer 1 is clamped between the polydimethylsiloxane and the wire mesh. The charge storage layer 1 is hot-pressed for 3-5 minutes at an ambient temperature of 110-150°C and a hot-pressing pressure of 3-5 MPa to form surface micro-wrinkles. By changing the hot-pressing temperature, pressure, and time, the morphology of the surface micro-wrinkles can be changed, and the resulting surface charge capture ability can be changed accordingly. Increasing the hot-pressing pressure or time increases the depth of the surface micro-wrinkles and forms a deeper charge capture energy well. As the hot-pressing temperature decreases, the elasticity of the charge storage layer 1 increases, and the thermal stress release during the hot-pressing process is enhanced, resulting in the formation of finer micro-wrinkles on the surface. The micro-wrinkle interface improves the net charge storage capacity.
[0010] Step 3: After hot pressing the charge storage layer 1, the first charge encapsulation layer 2-1, the charge storage layer 1, and the second charge encapsulation layer 2-2 are sequentially sandwiched and laminated from top to bottom, and then packaged at 110°C. Since the raw materials of the three layers are all high molecular weight polymers, the long polymer chains cross-link at high temperature, forming a three-layer sandwich structure. The hot pressing forms micro-wrinkles on the surface of the charge storage layer 1, and an array of pore cavities is formed between the first charge encapsulation layer 2-1 and the charge storage layer 1. The same array of pore cavities is also formed between the second charge encapsulation layer 2-2 and the charge storage layer 1.
[0011] Step 4: A thin electrode layer with a thickness of 20-100 nanometers is formed on the upper surface of the first charge encapsulation layer 2-1 and the lower surface of the second charge encapsulation layer 2-2 by a magnetron sputtering method, serving as the first electrode 3-1 and the second electrode 3-2 respectively; then, a corona polarization device is used to polarize the polymer film, and the corona needle tip releases a plasma with a large amount of charge under high pressure, and breaks through the pore cavity between the charge storage layer 1 and the first charge encapsulation layer 2-1 and the second charge encapsulation layer 2-2 to form a charge channel; after polarization, opposite-sign charges are attached to the upper and lower surfaces of the pore cavity, respectively, forming a macroscopic dipole array; the charges form a bipolar net charge rather than a unipolar charge through Paschen polarization; after the polymer film is subjected to pressure perpendicular to the membrane surface, the dipole moment of the dipole array changes significantly, thereby inducing charges of opposite signs and equal magnitude on the first electrode 3-1 and the second electrode 3-2.
[0012] Preferably, the electret material in step 1 is perfluoroethylene propylene, which has the following advantages in mechanics, dielectrics, and electret formation: in terms of mechanics, its flexibility gives it the advantage of forming and designing folds, and its advantages such as fatigue resistance, low friction coefficient and chemical corrosion resistance also make it more widely used; in terms of dielectrics, its low dielectric loss reduces heat loss, and its high insulation gives it a higher breakdown field strength; in terms of electrets, its perfluorinated properties give it good long-term charge retention and high charge density, as well as its strong ability to maintain charge under different temperatures, humidity and different environments, and its ability to be easily processed and prepared.
[0013] The electrode thin layer in step 4 uses a highly conductive material as a raw material.
[0014] The highly conductive material is made of single element gold, silver, platinum, poly (3,4-ethylenedioxythiophene): polystyrene sulfonic acid) or carbon nanotubes (CNTs). The above materials have both high conductivity and very low equivalent additional stiffness.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] 1. The present invention adopts a coordinated design of micro-corrugation design and corona breakdown to form a charge transfer channel, achieving a huge electromechanical coupling effect.
[0017] 2. The macroscopic dipole is generated by pore cavity polarization, which has a significant equivalent piezoelectric effect and a low elastic modulus of the material. It can also produce a huge charge output under very small external force input conditions.
[0018] 3. The present invention changes the surface shape of the pore cavity by hot pressing, and the designed surface shape is adjustable. By adjusting the hot pressing conditions, the equivalent piezoelectric coefficient of the polymer film can be controlled and designed.
[0019] 4. The present invention has a compact, lightweight and soft structure and has good compatibility with human body, underwater and other application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic structural diagram of the present invention
[0021] Figure 2 Schematic diagram of the explosion of the present invention
[0022] Figure 3 Schematic diagram of the micro-folds of the present invention and the equivalent piezoelectric effect principle
[0023] Figure 4 The preparation process of the present invention DETAILED DESCRIPTION
[0024] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] like Figure 1 and Figure 2 As shown, the present invention utilizes a micro-corrugation design to form a bipolar net charge composite polymer film with a huge equivalent piezoelectric effect, comprising a charge storage layer 1, a first charge encapsulation layer 2-1 and a second charge encapsulation layer 2-2 respectively attached to the upper and lower surfaces of the charge storage layer 1, a first electrode 3-1 attached to the upper surface of the first charge encapsulation layer 2-1, and a second electrode 3-2 attached to the lower surface of the second charge encapsulation layer 2-2; the surface of the charge storage layer 1 forms a surface micro-corrugation array through the release of thermal stress during the template hot pressing process, thereby improving the net charge storage capacity and the stability of large-scale long-term charge storage. The charge forms a bipolar net charge through Paschen polarization and is stored in the cavity between the first charge encapsulation layer 2-1, the second charge encapsulation layer 2-2, and the charge storage layer 1. The opposite-sign charges on the upper and lower surfaces of the cavity form a macroscopic dipole, which then produces a piezoelectric-like effect externally; by connecting the first electrode 3-1 and the second electrode 3-2 to an external circuit loop, the charge output under different stress conditions can be measured.
[0026] like Figure 3As shown, micro-wrinkles are formed on the upper and lower surfaces of the charge storage layer 1 after hot pressing. There are two ways in which micro-wrinkles are formed: one is the array concave-convex structure caused by the distributed pressure formed by the wire mesh on the charge storage layer 1. The other is the thermal stress caused by rapid heating and pressurization during hot pressing. The thermal stress in the film is released after the hot pressing is completed, resulting in the formation of tiny wavy wrinkles on the surface. The two types of wrinkles have different scales and together constitute micro-wrinkles with a large equivalent surface area. The first charge encapsulation layer 2-1 and the second charge encapsulation layer 2-2 are bonded to the charge storage layer 1 to form a large number of pore cavities, and provide a huge equivalent piezoelectric coefficient after corona poling.
[0027] like Figure 4 As shown, the method for preparing a bipolar net charge composite polymer film having a huge equivalent piezoelectric effect by using a micro-fold design comprises the following steps:
[0028] Step 1: Prepare a charge storage layer 1 and a first charge encapsulation layer 2-1 and a second charge encapsulation layer 2-2: The charge storage layer 1 uses a high molecular polymer material polyvinylidene fluoride-co-trifluoroethylene powder (PVDF-TrFE) as a raw material, which is dissolved in an organic solvent N,N-dimethylformamide (DMF), spin-coated on a flat substrate, and thermally precipitated at an ambient temperature of 70°C or above to form a polymer film with a thickness of 30-120 microns as the charge storage layer 1; the first charge encapsulation layer 2-1 and the second charge encapsulation layer 2-2 use an electret material, such as perfluoroethylene propylene (FEP), as a raw material, and are formed by chemical deposition, solution precipitation and other methods to form a polymer film with a thickness of 10-30 microns.
[0029] Step 2: After the charge storage layer 1 is prepared, it is hot-pressed using a wire mesh with different pore densities to form a surface micro-wrinkle array. Polydimethylsiloxane (PDMS) is used as a flexible hot-pressing substrate, and the charge storage layer 1 is clamped between the PDMS and the wire mesh. It is hot-pressed for 3-5 minutes at an ambient temperature of 110-150°C and a hot-pressing pressure of 3-5MPa to form surface micro-wrinkles. By changing the hot-pressing temperature, pressure, and time, the morphology of the surface micro-wrinkles can be changed, and the resulting surface charge capture ability will change accordingly. Increasing the hot-pressing pressure or time will increase the depth of the surface micro-wrinkles and form a deeper charge capture energy well. As the hot-pressing temperature decreases, the elasticity of the charge storage layer 1 increases, and the thermal stress release during the hot-pressing process is enhanced, then finer micro-wrinkles are formed on the surface, and the micro-wrinkle interface improves the net charge storage capacity.
[0030] Step 3: After hot pressing the charge storage layer 1, the first charge encapsulation layer 2-1, charge storage layer 1, and second charge encapsulation layer 2-2 are sandwiched and laminated from top to bottom. The resulting assembly is sealed at 110°C. Because all three layers are made of high-molecular-weight polymers, long-chain crosslinking occurs at high temperatures, resulting in a three-layer sandwich structure. Hot pressing creates micro-wrinkles on the surface of the charge storage layer 1, creating an array of pores and cavities between the first charge encapsulation layer 2-1 and the charge storage layer 1, and a similar array of pores and cavities between the second charge encapsulation layer 2-2 and the charge storage layer 1.
[0031] Step 4: Using methods such as magnetron sputtering, a thin electrode layer with a thickness of 20-100 nanometers is formed on the upper surface of the first charge encapsulation layer 2-1 and the lower surface of the second charge encapsulation layer 2-2, respectively, to serve as the first electrode 3-1 and the second electrode 3-2. The polymer film is then polarized using a corona poling device. The corona tip releases a highly charged plasma under high pressure, which penetrates the pores between the charge storage layer 1 and the first and second charge encapsulation layers 2-1 and 2-2, forming a charge channel. After polarization, charges of opposite sign attach to the upper and lower surfaces of the pores, forming a macroscopic dipole array. This charge is polarized to form a bipolar net charge, rather than a unipolar charge, through Paschen polarization. When the composite polymer film is subjected to pressure perpendicular to the film surface, the dipole array undergoes a significant change in dipole moment, inducing charges of equal magnitude and opposite sign on the first and second electrodes 3-1 and 3-2. Connecting the first and second electrodes 3-1 and 3-2 to an external circuit allows the charge output to be measured under different stress conditions.
[0032] The electrode thin layers of the first electrode 3-1 and the second electrode 3-2 use elemental gold (Au), silver (Ag), platinum (Pt) or other electrode metals and other conductive materials as raw materials, such as poly (3,4-ethylenedioxythiophene:polystyrenesulfonic acid) (PEDOT:PSS) or carbon nanotubes (CNTs).
Claims
1. A bipolar net-charge composite polymer film with a large equivalent piezoelectric effect is formed by micro-corrugation design, characterized by: The invention comprises a charge storage layer (1), a first charge encapsulation layer (2-1) and a second charge encapsulation layer (2-2) respectively attached to the upper surface and the lower surface of the charge storage layer (1), a first electrode (3-1) attached to the upper surface of the first charge encapsulation layer (2-1), and a second electrode (3-2) attached to the lower surface of the second charge encapsulation layer (2-2); the surface of the charge storage layer (1) forms a surface micro-wrinkle array through the release of thermal stress during the template hot pressing process, thereby improving the storage capacity of the net charge and the stability of the long-term storage of a large amount of charge; the charge forms a bipolar net charge through Paschen polarization and is stored in the cavity between the first charge encapsulation layer (2-1), the second charge encapsulation layer (2-2) and the charge storage layer (1); the opposite-signed charges on the upper and lower surfaces of the cavity form a macroscopic dipole, and then generate a piezoelectric effect to the outside; the first electrode (3-1) and the second electrode (3-2) are connected to an external circuit loop, so that the charge output under different stress conditions can be measured.
2. The bipolar net charge composite polymer film with a huge equivalent piezoelectric effect formed by utilizing a micro-corrugation design according to claim 1, characterized in that: Micro-wrinkles are formed on the upper and lower surfaces of the charge storage layer (1) after hot pressing. The micro-wrinkles are formed in two ways: one is the array concave-convex structure caused by the distributed pressure formed by the wire mesh on the charge storage layer (1); the other is the thermal stress caused by rapid heating and pressurization during hot pressing. The thermal stress in the film is released after the hot pressing is completed, resulting in the formation of tiny wavy wrinkles on the surface; the two wrinkles have different scales and together constitute micro-wrinkles with a large equivalent surface area; the first charge encapsulation layer (2-1) and the second charge encapsulation layer (2-2) are bonded to the charge storage layer (1), and the concave-convex structure of the micro-wrinkles forms a large number of pore cavities, and provides a huge equivalent piezoelectric coefficient after corona poling.
3. The method for preparing a bipolar net-charge composite polymer film having a huge equivalent piezoelectric effect by utilizing a micro-corrugation design according to claim 1 or 2, characterized in that: The steps include: Step 1: preparing a charge storage layer (1) and a first charge encapsulation layer (2-1) and a second charge encapsulation layer (2-2): the charge storage layer (1) uses a high molecular polymer material polyvinylidene fluoride-co-trifluoroethylene powder as a raw material, dissolves it in an organic solvent N,N-dimethylformamide, spin-coates it on a flat substrate, and heat-precipitates it at an ambient temperature of 70°C or above to form a polymer film with a thickness of 30-120 microns as the charge storage layer (1); the first charge encapsulation layer (2-1) and the second charge encapsulation layer (2-2) use an electret material as a raw material, and are formed by chemical deposition and solution precipitation methods to form a polymer film with a thickness of 10-30 microns; Step 2: After the charge storage layer (1) is prepared, a wire mesh with different pore densities is used for hot pressing to form a surface micro-wrinkle array. Polydimethylsiloxane is used as a flexible hot pressing substrate. The charge storage layer (1) is clamped between the polydimethylsiloxane and the wire mesh. The charge storage layer (1) is hot pressed for 3-5 minutes at an ambient temperature of 110-150° C. and a hot pressing pressure of 3-5 MPa to form surface micro-wrinkles. By changing the hot pressing temperature, pressure and time, the morphology of the surface micro-wrinkles can be changed, and the resulting surface charge capture ability is changed accordingly. Increasing the hot pressing pressure or time will increase the depth of the surface micro-wrinkles and form a deeper charge capture energy well. As the hot pressing temperature decreases, the elasticity of the charge storage layer (1) increases, the thermal stress release during the hot pressing process is enhanced, and finer micro-wrinkles are formed on the surface. The micro-wrinkle interface improves the net charge storage capacity; Step 3: After the charge storage layer (1) is hot-pressed, the first charge encapsulation layer (2-1), the charge storage layer (1), and the second charge encapsulation layer (2-2) are sequentially sandwiched and laminated from top to bottom, and the assembly is packaged at 110°C. Since the raw materials of the three layers are all high molecular polymers, long polymer chains are cross-linked at high temperature to form a sandwich structure of the three layers. Micro-wrinkles are formed on the surface of the charge storage layer (1) by hot pressing, and there are arrayed pore cavities between the first charge encapsulation layer (2-1) and the charge storage layer (1). At the same time, there are also arrayed pore cavities between the second charge encapsulation layer (2-2) and the charge storage layer (1). Step 4: A thin electrode layer with a thickness of 20-100 nanometers is formed on the upper surface of the first charge encapsulation layer (2-1) and the lower surface of the second charge encapsulation layer (2-2) by a magnetron sputtering method, serving as the first electrode (3-1) and the second electrode (3-2) respectively; then, a corona polarization device is used to polarize the polymer film, wherein the corona tip releases a plasma with a large amount of charge under high pressure, and breaks through the pore cavity between the charge storage layer (1) and the first charge encapsulation layer (2-1) and the second charge encapsulation layer (2-2), thereby forming a charge channel; after polarization, opposite-sign charges are attached to the upper and lower surfaces of the pore cavity, respectively, forming a macroscopic dipole array; the charges form a bipolar net charge rather than a unipolar charge through Paschen polarization; after the composite polymer film is subjected to pressure perpendicular to the film surface, the dipole moment of the dipole array changes significantly, thereby inducing charges of opposite signs and equal magnitude on the first electrode (3-1) and the second electrode (3-2).
4. The preparation method according to claim 3, wherein: The electret material in step 1 is perfluoroethylene propylene.
5. The preparation method according to claim 3, wherein: The electrode thin layer in step 4 uses a highly conductive material as a raw material.
6. The preparation method according to claim 5, characterized in that: The highly conductive material is simple gold, silver, platinum, poly (3,4-ethylenedioxythiophene): polystyrene sulfonic acid or carbon nanotubes (CNTs).